Faktor-Faktor Yang Mempengaruhi Struktur Modal Pada Perusahaan Manufaktur Yang Go Public - Nelyumna Nelyumna (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2016)
The purpose of this research was to analyze the influence of asset structure, liquidity, profitability, and firm size on capital structure. The sample used in this study is manufacturing company listed on the Indonesia Stock Exchange (IDX) 2012-2014. Samples were taken by purposive sampling technique. F test results indicate that the asset structure, liquidity, profitability, and firm size set significant effect on capital structure in manufacturing company listed on the Indonesia Stock Exchange (IDX) with a confidence level of 95%. t test results showed that variables asset structure, liquidity, profitability, and firm size thatsignificantly affect the capital structure of the companies listed in Indonesia Stock Exchange (IDX) with a confidence level of 95%.